Thrombotic Microangiopathy with Skin Localization Secondary to Cytarabine-Daunorubicin Association: Report of a Case - S. Regragui; S. Amelal; S. Astati; M. Zine; N. Alami Drideb; A. Al Bouzidi; N. Messaoudi; M. Benkirane; K. Doghmi; M. Mikdame (Case Reports in Hematology)
The thrombotic microangiopathy is a syndrome characterized by the combination of mechanical hemolytic anemia, peripheral thrombocytopenia, and organ failure of variable severity. In addition to the idiopathic form, several cases are identified as secondary to pregnancy, infections, disease systems, organ transplants, and cancer. Other forms are secondary to drugs including antimitotics. We report the case of a patient followed for acute myelogenous leukemia. She received induction chemotherapy combining daunorubicin and cytarabine, complicated by thrombotic thrombocytopenic purpura.